A phase II study of outpatient first-line paclitaxel, carboplatin, and bevacizumab for advanced-stage epithelial ovarian, peritoneal, and fallopian tube cancer. Issue 4 (1st July 2007) - Micha, J. P.; Goldstein, B. H.; Rettenmaier, M. A.; Genesen, M.; Graham, C.; Bader, K.; Lopez, K. L.; Nickle, M.; Brown, J. V.
Abstract : The purpose of this study was to assess the response rate and toxicity of paclitaxel, carboplatin, and bevacizumab (PCB) primary induction therapy for the treatment of advanced-stage ovarian carcinoma. Twenty patients were treated with paclitaxel (175 mg/m 2 ), carboplatin (AUC of 5 IV), and bevacizumab (15 mg/kg) of body weight; q21 days for six cycles. Bevacizumab was administered at cycles two through six. Patients received 116 cycles of PCB chemotherapy (median = 6, range 2–6) and were evaluable for toxicity assessment. Grade 3 and 4 neutropenia developed in 23.3% and 25% of cycles, with no incidence of grades 3/4 thrombocytopenia or anemia. Prior to cycle six, one patient was removed from the study due to grade 3 neuropathy and another patient was excluded due to clinical deterioration. There was no incidence of gastrointestinal perforations, and only two patients demonstrated grade 3 hypertension (HTN). No grade 4 HTN was observed. Eighteen patients were evaluated for response following induction therapy. Six demonstrated a complete response (30%) and ten exhibited a partial response (50%), resulting in a total response rate of 80%. One patient exhibited stable disease (5%), and one demonstrated disease progression (5%). The lack of bowel perforations and wound complications should mitigate some concerns regarding these side effects. This study suggests that first-line treatment with PCB can be safely administered to previously untreated advanced-stage ovarian carcinoma patients. The favorable toxicity results and reasonable response rate warrant additional study in a larger patient population.